Review of input and output policies for cereal production in Bangladesh - Pullabhotla, Hemant; Ganesh-Kumar, Anand (International Food Policy Research Institute, 2012)
Even as Bangladesh struggles to achieve food security, the country’s cereal sector faces new challenges. What are these challenges and what should be the country’s response? With these questions in mind, this paper reviews the key policies of agricultural inputs and outputs in Bangladesh that are crucial for improving cereal production in the country.